G-CSF and G-CSFR Induce a Pro-Tumorigenic Macrophage Phenotype to Promote Colon and Pancreas Tumor Growth - Ioannis Karagiannidis (Cancers, 2020)
Tumor-associated macrophages (TAMs) in the gastrointestinal tumor microenvironment (TME) are known to polarize into populations exhibiting pro- or anti-tumoral activity in response to stimuli such as growth factors and cytokines. Our previous work has recognized granulocyte colony-stimulating factor (G-CSF) as a cytokine capable of influencing immune cells of the TME exhibiting pro-tumoral activity. Here, we aimed to focus on how G-CSF regulates TAM phenotype and function and the effects on gastrointestinal (GI) tumor progression. Thus, wildtype (WT) and G-CSFR−/− macrophages were examined for cytokine production, gene expression, and transcription factor activity. Adoptive transfer of WT or G-CSFR−/− macrophages into tumor-bearing mice was performed to study their influence in the progression of colon (MC38) and pancreatic (PK5L1940) tumor mouse models. Finally, the difference in cytotoxic potential between WT and G-CSFR−/− macrophages was examined both in vitro and in vivo. Our results indicate that G-CSF promotes increased IL-10 production and decreased IL-12 production, which was reversed in G-CSFR−/− macrophages for a pro-inflammatory phenotype. Furthermore, G-CSFR−/− macrophages were characterized by higher levels of NOS2 expression and NO production, which led to greater tumor related cytotoxicity both in vitro and in vivo. Our results suggest that in the absence of G-CSFR, macrophage-related tumor cytotoxicity was amplified. These findings, along with our previous reports, pinpoint G-CSF /G-CSFR as a prominent target for possible clinical applications that aim to control the TME and the GI tumor progression.